Being Digital Native, Digital Immigrant and Digital Hybrid in Terms of Teaching Profession - Şad, Süleyman Nihat; Durmuş, Vildan (Behçet ORAL, 2017)
The present study aimed to investigate to what extent the preservice and inservice teachers have the characteristics of digital natives, digital immigrants and digital hybrids. The study also examined these characteristics in terms of variables like data of birth, gender and being a preservice or inservice teacher. The study was conducted on 263 inservice teachers from different subject fields working in the province of Elazığ and 289 preservice teachers attending to different departments of educational faculty of Fırat University during 2012-2013 academic year. In this study, which was conducted in accordance with descriptive and associational survey designs, the data were collected using “Digital Native, Digital Immigrant, and Digital Hybrid Teacher Scale” originally developed by the researchers. Obtained data were analysed using frequencies, percentages, one-way ANOVA and Chi-square tests. The analysis revealed that, according to the scores obtained from the factor Arrangement of Learning Settings, 102 (18,5%) of the participants fell into the category of Digital Immigrants (DI), 297 (53,8%) fell into the category of Digital Hybrid (DH) and 153 (27,7%) fell into the category of Digital Natives (DN). According to their preferences regarding Communication with Parents and Children, 358 (64,9%) of the participants fell into the category of Digital Immigrants (DI), 154 (27,9%) fell into the category of Digital Hybrid (DH) and only 40 (7,2%) fell into the category of Digital Native (DN). For the last factor, in terms of their Personal and Professional Development preferences, 224 (40,6%) of the participants fell into the category of Digital Immigrant (DI), 258 (46,7%) fell into the category of Digital Hybrid (DH) and only 70 (12,7%) of them fell into the category of Digital Natives (DN). Also findings and discussions were presented regarding the participants’ preferences in relation to their gender, age, and being a pre- or in-service teacher.

Bu araştırmada, öğretmen ve öğretmen adaylarının dijital yerlilik, dijital göçmenlik ve dijital melezlik özelliklerinin incelenmesi amaçlanmıştır. Ayrıca bu özellikler doğum tarihi, cinsiyet ve öğretmen ya da öğretmen adayı olma değişkenleri açısından incelenmiştir. Araştırma Elazığ il merkezinde 2012-2013 öğretim yılında görev yapan çeşitli branşlara mensup 263 öğretmen ve Fırat Üniversitesi Eğitim Fakültesinde öğrenim gören 289 öğretmen adayı ile yürütülmüştür. Betimsel ve ilişkisel tarama desenlerine göre yürütülen araştırmada veriler, araştırmacılar tarafından geliştirilen “Dijital Yerli, Dijital Göçmen ve Dijital Melez Öğretmen Ölçeği” ile toplanmıştır. Verilerin analizinde frekans, yüzde, tek yönlü ANOVA ve Ki-Kare tekniklerden yararlanılmıştır. Araştırma sonucunda, araştırmaya katılan 552 öğretmen ve öğretmen adayından 102’sinin (%18,5) Öğrenme Ortamlarını Düzenleme boyutundan aldıkları puanlar açısından Dijital Göçmen (DG), 297’sinin (%53,8) Dijital Melez (DM) ve 153’ünün de (%27,7) Dijital Yerli (DY) kategorisine girdiği anlaşılmıştır. Veli ve Öğrenciyle İletişim kurma tercihleri açısından katılımcıların 358’si (%64,9) Dijital Göçmen (DG), 154’ü (%27,9) Dijital Melez (DM) ve sadece 40’ı (%7,2) Dijital Yerli (DY) kategorisine girmektedir. Son olarak Kişisel ve Mesleki Gelişim tercihleri açısından katılımcıların 224’ü (%40,6) Dijital Göçmen (DG), 258’i (%46,7) Dijital Melez (DM) ve sadece 70’i (%12,7) Dijital Yerli (DY) kategorisine girmektedir. Çalışmada ayrıca görev türü, cinsiyet ve yaş değişkenlerine ilişkin bulgular sunularak sonuçlar tartışılmıştır.
ÖĞRETMENLİK MESLEĞİ BAĞLAMINDA DİJİTAL YERLİLİK, DİJİTAL GÖÇMENLİK VE DİJİTAL MELEZLİK